Central Retinal Vein Occlusion after COVID-19 Infection - Nguyen, Ngoc-Chau Isabelle; Eandi, Chiara; Guex-Crosier, Yan (Klinische Monatsblätter für Augenheilkunde, 2023)
Introduction Central retinal vein occlusions are not well-known complications of SARS-CoV-2 infection. We describe a case of central retinal vein occlusion secondary to COVID-19, and a review of the literature was performed.History and Signs A 47-year-old woman with no underlying ocular or medical condition presented to the hospital complaining about sudden onset of multiple scotomas in her left eye. A COVID-19 infection was confirmed 2 days previously by a PCR test that was performed 2 days after the onset of symptoms. Medical history revealed no risk factors and no oral contraception. Her best-corrected visual acuity was 1.0 in the right eye and 0.04 in the left eye. Clinical exam showed a left relative afferent pupillary defect and a nasally localized papilledema on fundoscopy of the left eye. Multiple dot and blot hemorrhages were also present. Optical coherence tomography revealed cystoid macular edema and paracentral acute middle maculopathy. The results of the fluoresceine angiography were consistent with central retinal vein occlusion. Laboratory workup later revealed an elevated fibrinogen level, corresponding to the COVID-19-induced hypercoagulable state. No other prothrombotic conditions were found. The patient immediately received an intravitreal injection of Lucentis (ranibizumab) after diagnosis. Complete resolution of the retinal hemorrhages and papilledema was observed 1.5 months after treatment and the final visual acuity was 1.25 in the left eye.Conclusion Coagulation abnormalities are frequently observed in infectious diseases such as COVID-19 infection and the resulting prothrombotic state can sometimes lead to retinal vascular complications, including central retinal vein occlusion, irrespective of the presence of other classical risk factors. The consideration of this information could help clinicians establish a prompt diagnosis and therefore appropriate treatment, which could hopefully lead to complete healing of retinal lesions.
Keywords: retina; COVID-19; central retinal vein occlusion; paracentral acute middle maculopathy